2018
DOI: 10.3389/fimmu.2018.01167
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein (CRP) and Leptin Receptor in Obesity: Binding of Monomeric CRP to Leptin Receptor

Abstract: While leptin deficiency or dysfunction leads to morbid obesity, obese subjects are characterized paradoxically by hyperleptinemia indicating lack of response to leptin. C-reactive protein (CRP) has been suggested to be a key plasma protein that could bind to leptin. To examine whether CRP interferes with leptin action, mediated through its cell surface receptor, docking studies of CRP with the extracellular domain of the leptin receptor were done employing bioinformatics tools. Monomeric CRP docked with better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 69 publications
1
40
0
3
Order By: Relevance
“…Due to the high abundance of MAIT cells in the liver, we speculated that BAs may have a modulatory function on the bacterial activation of these cells. Furthermore, there are reports showing that obesity is associated with alterations in MAIT cell function and distribution in human adults as well as with alterations in inflammatory markers such as C‐reactive protein (CRP), macrophage inflammatory proteins (MIP)‐1α and interleukin (IL)‐8 and the expression of chemokine receptor (CXCR3). Thus, the relationship between BA concentrations, MAIT cell activation and inflammatory parameters with regard to weight was the focus of our present investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high abundance of MAIT cells in the liver, we speculated that BAs may have a modulatory function on the bacterial activation of these cells. Furthermore, there are reports showing that obesity is associated with alterations in MAIT cell function and distribution in human adults as well as with alterations in inflammatory markers such as C‐reactive protein (CRP), macrophage inflammatory proteins (MIP)‐1α and interleukin (IL)‐8 and the expression of chemokine receptor (CXCR3). Thus, the relationship between BA concentrations, MAIT cell activation and inflammatory parameters with regard to weight was the focus of our present investigation.…”
Section: Introductionmentioning
confidence: 99%
“…CRP is currently a hot spot for studying inflammation and related diseases. [30][31][32] Our results showed that elevated CRP was associated with those groups that received antibiotic compared with the control group.…”
Section: Discussionmentioning
confidence: 52%
“…analyzed the whole genome sequence database of the Atlantic salmon (Salmo salar) and identi ed ve CRP/serum amyloid P-component (SAP) like molecules, CRP/SAP-1a, CRP/SAP-1b, CRP/SAP-1c, CRP/SAP-2, and CRP/SAP-3 [60]. CRP is a novel topic for studying in ammation and related diseases [61][62][63], being associated with chronic in ammation; thus, here CRP was examined in the abdominal blood of the SD rats. The results showed that elevated CRP was associated with groups receiving antibiotics, as with the discussed in ammatory factors.…”
Section: Discussionmentioning
confidence: 99%